Characteristic of body scrub based Ulva lactuca seaweed salt residue with addition Aloe vera gel - Nurjanah Nurjanah; Abdullah Asadatun; Jati Faradilla Ratna; Seulalae Anggrei Viona; Afifah Zahrah (BIO Web of Conferences)
Ulva lactuca salt residue can act as a natural scrub to replace the microbeads. The combination with Aloe vera gel can improve the function of body scrubs on the skin. This study aimed to determine the optimal concentration of A. vera gel for making body scrubs from U. lactuca seaweed salt residue based on physical properties, total phenolic content and antioxidant activity. Body scrub was formulated by adding 7% U. lactuca salt residue and A. vera gel at concentrations of 0, 3, 5, and 7%. The parameters analyzed included the pH, viscosity, emulsion stability, humidity, spreadability, homogeneity, hedonic test, total phenolics, and antioxidants using the DPPH method. The results showed that differences in A. vera gel concentrations did not significantly affect the preferences of the panelists (aroma, colour, texture, appearance). Spreadability, pH, and viscosity of body scrub ranged from 4.02-4.55 cm; 6.38-6.53; and 8,600- 13,160 cP, respectively. Body scrub with A. vera gel can increase the humidity with stable emulsion physical properties and a homogeneous mixture of ingredients. The best treatment was the addition of 3% A. vera with antioxidant activity of IC50 value, namely 278.02 ppm and the highest total phenolic of 0.528 mg GAE/g.